2016
DOI: 10.1620/tjem.240.147
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Human Papillomavirus Vaccine for Prevention of Cervical Abnormalities in Miyagi, Japan

Abstract: Prevention of cervical cancer has been unsuccessful in Japan because of low rates of cancer screening and vaccination. The Vaccine Adverse Review Committee of the Japanese Government investigated 2,475 adverse events and reported 617 (6.9/100,000) severe cases and 176 (2.0/100,000) cases with chronic pain. The proactive recommendation for human papillomavirus (HPV) vaccination has been suspended since June 2013. In this study, we examined vaccination rate and incidence of abnormal cervical cytology in women ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…It is likely that the vaccination rate decreases with aging. These data, however, are very similar to those reported by Ozawa et al They reported that the vaccination rate in the same age groups of women who underwent cervical cancer screening was 42.3%, 10.0%, 17.5%, 3.8%, and 4.0%, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is likely that the vaccination rate decreases with aging. These data, however, are very similar to those reported by Ozawa et al They reported that the vaccination rate in the same age groups of women who underwent cervical cancer screening was 42.3%, 10.0%, 17.5%, 3.8%, and 4.0%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Approximately 4 years have passed since the public HPV vaccination program was initiated; thus, women aged 20–24 years who have possibly received the public HPV vaccine have since undergone cervical cancer screening. Nonetheless, limited studies have investigated the effect of HPV vaccination on cervical cytologic abnormalities . Therefore, aim of the present study was to compare the prevalence of abnormal cytology results during cervical cancer screening in women aged 20–24 years who have received HPV vaccination and those who have not in the Akita Prefecture between 2014 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The rates in FY 2014 were recalculated from the data published in the earlier report (Ozawa et al 2016). In FY 2015, the overall vaccination rate was 25.41% for women aged 20 to 24 years old, and the rates of vaccination were 59.26%, 49.68%, 11.97%, 9.08%, and 4.58% in those aged 20, 21, 22, 23, and 24 years old, respectively, with the exclusion of the 538 women ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The rates of FY 2014 were recalculated from the data published in the earlier report (Ozawa et al 2016) and are presented for comparison. (Ozawa et al 2016). cination and 1.14% (56/4,922) in those without vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation